Development of a Low-fish Meal Feed Formulation for Commercial Production of Litopenaeus vannamei - M. Fox, Joe; L. Lawrence, Addison; Smith, Franz (Facultad de Ciencias Biologicas, 2019)
Fish meal is used in marine shrimp feeds because it is high in protein, highly digestible and is an effectivefeed attractant. Reasons for current interest in its replacement include irregular availability, variable quality,perceived contribution to deterioration of fisheries, potential for adulteration, contamination withhydrocarbons and biological pathogens, and increasing cost. Growth trials were conducted with juvenileLitopenaeus vannamei to evaluate modifications in nutrient supplementation/restriction of a basal fish mealreplacement formula at the 50% replacement level. Trials compared growth and survival of shrimp fed abasal control feed to experimental feeds in which crystalline amino acids (CAA), oil and lecithin, blood mealand specific minerals were modified. Improved or similar growth relative to the control feed were shownwith reduced levels of CAA, removal of menhaden oil, inclusion of a lower level of lecithin, and maintenanceof blood meal and mineral supplements at their basal levels. This information was used to develop ageneralized fish meal replacement formulation for marine penaeid shrimp using readily available partiallypurifiedingredients. Low- and high-marine animal meal feed formulations are compared.